ACM's Remote Proctoring Software Guidelines. (Communications of the ACM, 2023)
The article announces that ACM’s U.S. Technology Policy Committee (USTPC) has released a statement on "Principles for the Development and Deployment of Equitable, Private, and Secure Remote Proctoring Systems."